2006
DOI: 10.1021/jp057300t
|View full text |Cite
|
Sign up to set email alerts
|

The Complexes between CH3OH and CF4. Infrared Matrix Isolation and Theoretical Studies

Abstract: The complex formed between methanol and tetrafluoromethane has been identified in argon and neon matrixes by help of FTIR spectroscopy. Three fundamentals (nu(OH), nu(FCF), and nu(CO)) were observed for the complex isolated in the two matrixes, and the OH stretch was red shifted in a neon matrix and blue shifted in an argon matrix with respect to the corresponding vibration of the methanol monomer. The theoretical studies of the structure and spectral characteristics of the complexes formed between CH(3)OH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This temperature may be the room temperature at which the deposition of the two gases is performed, the room temperature proportion between HNCO a (t=0) and HNCO na (t=0) is frozen when the molecular solid is condensed onto the cold surface. At a 300 K room temperature, we found a difference in Gibbs energy of 4.3 kJ mol −1 , which is on the order of magnitude of a molecular reorientation (Mielke et al 2006(Mielke et al , 2008. This means that our ice analogs, made from a room temperature gas quenching into an amorphous solid, are out of equilibrium.…”
Section: Kinetic Studies Of the Hnco + Nh 3 Reaction Using A Rate Equmentioning
confidence: 73%
“…This temperature may be the room temperature at which the deposition of the two gases is performed, the room temperature proportion between HNCO a (t=0) and HNCO na (t=0) is frozen when the molecular solid is condensed onto the cold surface. At a 300 K room temperature, we found a difference in Gibbs energy of 4.3 kJ mol −1 , which is on the order of magnitude of a molecular reorientation (Mielke et al 2006(Mielke et al , 2008. This means that our ice analogs, made from a room temperature gas quenching into an amorphous solid, are out of equilibrium.…”
Section: Kinetic Studies Of the Hnco + Nh 3 Reaction Using A Rate Equmentioning
confidence: 73%
“…The most significant results on this field have been obtained using the vibrational spectroscopy (FTIR absorption and Raman) together with trapping/isolation in various cryogenic matrices [4][5][6][7][8][9][10][11][12][13][14]. This is mainly because the spectral acquisition carried out on isolated clusters at very low temperatures causes the appearance of narrow peaks with minimal band overlapping.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3, interestingly, the gas phase calculations show that the TiH 2 scissor and wag frequencies are nearly degenerate (612.4 vs. 613.9 cm -1 ) while the argon matrix calculations indicate that the two frequencies are just like a doublet (594.1 vs. 600.1 cm -1 ). This point should be paid more attention to during the assignment of the experimental frequencies since the doublets may be easily explained to be due to the matrix site effect [4,9,10,34]. Note that the experimental argon matrix frequency 588.5 cm -1 was only assigned to the TiH 2 wag mode of their calculation (616.8 cm -1 ) [3].…”
Section: Resultsmentioning
confidence: 98%
“…However, the existing calculations are not in exact consistency with the experiments because the experimental frequencies were measured from the R 2 MH 2 molecules isolated in the rare gas matrix while the calculations were based on a gas phase model and the matrix effect was not modelled. Existing experiments have demonstrated that the rare gas matrix has an evident effect on the infrared fundamental frequencies of a single molecule [7][8][9] and that, sometimes, the matrix effect can even change the relative magnitude of two vibrational frequencies [9,10]. As a consequence, the modelling of the rare gas matrix effect should be of great significance for understanding the experimental matrix isolation infrared spectra of the R 2 MH 2 molecules.…”
Section: Introductionmentioning
confidence: 99%